1995
DOI: 10.1007/bf01710051
|View full text |Cite
|
Sign up to set email alerts
|

Severity of multiple organ failure (MOF) but not of sepsis correlates with irreversible platelet degranulation

Abstract: Multiple hemostatic changes occur in sepsis and multiple organ failure (MOF). To evaluate the role of platelets in patients with sepsis and MOF, we examined changes in surface glycoproteins on circulating platelets of 14 patients with suspected sepsis and MOF. The severity of sepsis and MOF was assessed by the Elebute and APACHE II scoring systems, respectively. Using flow cytometric techniques and platelet specific monoclonal antibodies, platelet surface expression of fibrinogen receptor on GPIIb-IIIa, of von… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…17,18,21,25 In sepsis, it has been demonstrated that platelets show enhanced adherence to leukocytes 17 and are activated, 18 although the severity only of multiorgan failure, but not of sepsis, correlates with irreversible platelet activation. 26 Under experimental flow conditions, platelets seem to interact preferentially with monocytes rather than PMNs, which are dependent on divalent cations and the expression of PSGL-1 and in part also on ␤1-and ␤2-integrins for fMLP-activated monocytes. 27,28 However, after severe trauma or sepsis, platelets associate significantly with both monocytes as well as PMNs.…”
Section: Discussionmentioning
confidence: 91%
“…17,18,21,25 In sepsis, it has been demonstrated that platelets show enhanced adherence to leukocytes 17 and are activated, 18 although the severity only of multiorgan failure, but not of sepsis, correlates with irreversible platelet activation. 26 Under experimental flow conditions, platelets seem to interact preferentially with monocytes rather than PMNs, which are dependent on divalent cations and the expression of PSGL-1 and in part also on ␤1-and ␤2-integrins for fMLP-activated monocytes. 27,28 However, after severe trauma or sepsis, platelets associate significantly with both monocytes as well as PMNs.…”
Section: Discussionmentioning
confidence: 91%
“…Platelet formation from megakaryocytes is an important determinant of the platelet size (21), although to the best of our knowledge, no studies have investigated changes in platelet formation in patients with severe sepsis. The release of platelet granules, another factor influencing the platelet size, was found to be elevated in severely septic patients with multiple organ failure (22), although that study included cardiovascular patients. We assume that changes in the MPV levels may be attributed to a combination of several factors, including decreases in platelet formation by megakaryocytes, platelet consumption in peripheral tissue and degranulation in larger platelets, and that the impact of inflammation on MPV elevation after BSI in nonsurvivors is stronger than that observed in survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of both leukocytes and platelets is commonly observed in sepsis. There is increasing evidence that activation of these cells contributes to the development of disseminated intravascular coagulation (DIC) and multiple organ failure, as blood flow and consequent oxygen delivery is reduced and activation of both pro-and anti-inflammatory cytokine networks are induced [71,74]. CD62P is increased on platelets from septic versus non-septic patients [75,76] and activated platelets release platelet microparticles (MP) that express functional surface receptors that allow them to adhere to leukocytes [76].…”
Section: Sepsismentioning
confidence: 99%